2009
DOI: 10.1186/1756-9966-28-155
|View full text |Cite
|
Sign up to set email alerts
|

A novel Bifidobacterium infantis-mediated TK/GCV suicide gene therapy system exhibits antitumor activity in a rat model of bladder cancer

Abstract: Bladder cancer is the ninth most common malignancy in the world. Successful clinical management remains a challenge. In order To search for novel targeted and efficacious treatment, we sought to investigate anti-tumor activity of BI-TK suicide gene therapy system in a rat model of bladder tumors. We first constructed and tested an anaerobic Bifidobacterium infantis-mediated thymidine kinase (BI-TK) suicide gene therapy system. To test the in vivo efficacy of this system, we established a rat model of bladder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 18 publications
3
45
0
1
Order By: Relevance
“…26 Numerous publications provide convincing evidence that genera of bacteria including Bifidobacterium and commensal Escherichia coli have potential in cancer therapy. 9,10,12,16,[27][28][29][30] This vector class compares favorably with other vectors in terms of key attributes such as safety, ease of manipulation, and production. While nonpathogenic bacteria have yet to enter clinical trial in the context of tumor targeting vectors, existing knowledge strongly indicates their suitability as a vector system for clinical use.…”
Section: Bacterial-mediated Tumor Therapymentioning
confidence: 99%
“…26 Numerous publications provide convincing evidence that genera of bacteria including Bifidobacterium and commensal Escherichia coli have potential in cancer therapy. 9,10,12,16,[27][28][29][30] This vector class compares favorably with other vectors in terms of key attributes such as safety, ease of manipulation, and production. While nonpathogenic bacteria have yet to enter clinical trial in the context of tumor targeting vectors, existing knowledge strongly indicates their suitability as a vector system for clinical use.…”
Section: Bacterial-mediated Tumor Therapymentioning
confidence: 99%
“…41,42,57,67,68 These suicide genes effectively converts non-toxic prodrugs into their highly cytotoxic forms: 65,69,70 CD converts 5-fluorocytosine into 5-fluorouracil, carboxylesterase, CPT-11, SN-38 and herpes simplex virus thymidine-kinase, ganciclovir (GCV), active form of GCV. 62,64,67,69,71,72 For example, Gu et al 73 evaluated the efficacy of the herpes simplex virus thymidine-kinase/GCV system using MSCs (MSCtk cells) in leptomeningeal glioma dissemination models. The results from this study showed that MSCtk cells exerted a strong 'bystander effect' both in vitro and in vivo conditions in the presence of GCV.…”
Section: Non-engineered Stem Cells Transplantation Strategiesmentioning
confidence: 99%
“…In a different report, Fujimori et al created a plasmid encoding the CD gene and used it to transform Bifidobacterium longum in a system termed Bifidobacterial Selective Targeting-Cytosine Deaminase therapy. In another enzyme-prodrug strategy, the Herpes Simplex VirusThymidine Kinase (HSV-TK) gene was transformed into Bifidobacterium infantis to create the Herpes Simplex Virus-Thymidine Kinase/Ganciclovir (HSV-TK/GCV) system [13]. Thymidine kinase expressed in bacteria that specifically colonize tumor tissues can convert the non-toxic precursor ganciclovir into ganciclovir-3-phosphate, a toxic substance that kills tumor cells.…”
Section: Delivery Of Engineered Toxins or Pro-drugsmentioning
confidence: 99%
“…Although some of these organisms are used as monotherapy [6,8,24], most of them are used as vehicles to deliver therapeutic agents such as DNA [19], siRNA [9,28], toxins [7, 10-12, 20, 30], and prodrug-enzymes [13], or combined with other therapies [14,15,21,32] to enhance their therapeutic effect.…”
Section: Cancer Treatment Strategies Based On the Use Of Bacteriamentioning
confidence: 99%